EMON SANG PEDOFIL - Nantia Rena Munggaran; Zaki Zulfikar (Dialektika, 2016)
Cases of sexual assault on a child that occurred in 2014 so alarmed the people of Indonesia. Pedophilia in Sukabumi killed up to 114 children. The author tries to analyze 15 text news about sexual abuse of children by Emon contained in HU HU Mind and Tribune Jabar during the month of May 2014. The method used is a qualitative method approach constructivist perspective . To analyze the data analysis method framing Robert N. Entman models that explore aspects of the news of problem identification , causal interpretation , moral evaluation, and treatment recommendation. From the analysis conducted there are differences in the framing of the news by the media.